The Tyrosine-Autokinase UbK Is Required for Proper Cell Growth and Cell Morphology of Streptococcus pneumoniae - Pelletier, Anaïs; Freton, Céline; Gallay, Clément; Trouve, Jennyfer; Cluzel, Caroline; Franz-Wachtel, Mirita; Macek, Boris; Jault, Jean-Michel; Grangeasse, Christophe; Guiral, Sébastien (Frontiers in Microbiology, 2019)
Protein phosphorylation is a key post-translational modification required for many cellular functions of the bacterial cell. Recently, we identified a new protein-kinase, named UbK, in Bacillus subtilis that belongs to a new family of protein-kinases widespread in bacteria. In this study, we analyze the function of UbK in Streptococcus pneumoniae. We show that UbK displays a tyrosine-kinase activity and autophosphorylates on a unique tyrosine in vivo. To get insights into its cellular role, we constructed a set of pneumococcal ubk mutants. Using conventional and electron microscopy, we show that the ubk deficient strain, as well as an ubk catalytic dead mutant, display both severe cell-growth an cell-morphology defects. The same defects are observed with a mutant mimicking permanent phosphorylation of UbK whereas they are not detected for a mutant mimicking defective autophosphorylation of UbK. Moreover, we find that UbK phosphorylation promotes its ability to hydrolyze ATP. These observations show that the hydrolysis of ATP by UbK serves not only for its autophosphorylation but also for a distinct purpose essential for the optimal cell growth and cell-morphogenesis of the pneumococcus. We thus propose a model in which the autophosphorylation / dephosphorylation of UbK regulates its cellular function through a negative feedback loop.